Mutations in the Interleukin-15 Gene as a Molecular Biomarker in the Atherosclerosis Disease. - Sarbaz I. Mohammed (Zanco Journal of Pure and Applied Sciences, 2023)
The present study investigated the association between mutations in the gene of interleukin (IL)-15 located on exon 8 and the risk of atherosclerosis in Iraqi patients. A total of 87 patients (71 males and 16 females) with atherosclerosis prior to [Coronary Artery Bypass Graft (CABG) surgery] median age, 57 years and 30 subjects with no CVD (median age, 58.5 years) were enrolled at the Surgical Specialty Hospital of Cardiac Center-Erbil-Iraq between April 2021 and February 2022. Genotype analysis was achieved using a polymerase chain reaction (PCR) and Sanger DNA sequencing and clinical biochemistry were achieved by Cobas 311and e411 analyzers. The IL-15 homozygous rs2291596 (53.3%) and rs10833 (100%) genotypes appeared in peak frequencies and were related to a risk of the progress of atherosclerosis. In comparison, the remaining two novel mutations exhibited a low frequency for the 97264 G>GC genotype (13.3%) and the 97270 G>GT genotype (26.7%). Significant changes were observed in serum C-reactive protein (CRP) levels, the erythrocyte sedimentation rate (ESR), and high-density lipoprotein (HDL), alkaline phosphatase (ALP), blood fasting glucose, hemoglobin A1c (HbA1c) and troponin T-hs levels in the patients with atherosclerosis compared with those of the non-CVD subjects. Finally, it was concluded that the IL-15 mutations may play an essential role in the development and prognostic prediction of blood vessel atherosclerosis.